CIMPA DAN NILAI KEBERSAMAAN DALAM KERJA TAHUN - Fadli Abidin Harahap; Yummi Jumiati Marsa (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2025)
This study aims to determine the value of togetherness contained in cimpa in the work year activities of the Karo tribe. Data collection in this study used a qualitative method with an Ethnographic approach. Data collection techniques in this study were observation, interviews, and documentation. Data analysis techniques in this study were data reduction, data presentation, and drawing conclusions. This study examines the value of togetherness contained in cimpa in the Kerja Tahun activities of the Karo tribe. The purpose of this study was to obtain information about how the Kerja Tahun tradition activities are in Karo Regency, Tiga Panah District, in Suka Village along with the values of togetherness contained in cimpa (a typical Karo tribe food). The results of this study indicate that Kerja Tahun is a traditional tradition celebrated by the Karo Community which is carried out in all areas in Karo Regency. The Kerja Tahun tradition teaches the values of togetherness contained in it. In each process of the Kerja Tahun tradition activity has its own meaning, the togetherness in question is that families who are outside the area will gather in one house to follow the Kerja Tahun tradition